2006
DOI: 10.1103/physrevc.73.025805
|View full text |Cite
|
Sign up to set email alerts
|

Low-density instabilities in relativistic asymmetric matter of compact stars

Abstract: Dynamical instability modes of low-density asymmetric nuclear matter (ANM) neutralized by electrons as found in supernova core and neutron star crust are studied in the framework of relativistic mean-field hadron models with the inclusion of electron and photon fields. The dynamical and thermodynamical instability zones are compared. It is shown that the Coulomb field quenches large structure formation but has little effect on medium and small-size fluctuations that are, however, partially stabilized by the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
86
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 44 publications
8
86
0
Order By: Relevance
“…It is shown that pasta clusters in β equilibrium completely melt for temperatures above 5 to 6 MeV. These results agree partially with the predictions obtained within a dynamical spinodal (DS) approach [24][25][26]. A similar calculation was done with Skyrme forces in Ref.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…It is shown that pasta clusters in β equilibrium completely melt for temperatures above 5 to 6 MeV. These results agree partially with the predictions obtained within a dynamical spinodal (DS) approach [24][25][26]. A similar calculation was done with Skyrme forces in Ref.…”
Section: Introductionsupporting
confidence: 80%
“…In the latter case, the crust-core transition is defined by the intersection between the β-equilibrium EoS and the dynamical spinodal (DS). The cluster size is identified with half the wavelength of the density fluctuation [24,25,27]. The results are shown in Fig.…”
Section: Finite-temperature Effects On Crustmentioning
confidence: 93%
See 1 more Smart Citation
“…[17] and references therein. Matter is stable to fluctuations in density and composition, under conditions of constant volume and temperature, when the free energy density F is a convex function of the proton and neutron densities.…”
Section: B Thermodynamical Instabilitiesmentioning
confidence: 99%
“…The nuclear pasta phases can be thought of as arising due to unstable collective modes in uniform matter [14], with the transition to uniform matter studies by analyzing the dynamical and thermodynamical spinodals in density and temperature space [15][16][17][18]. To study the details of the pasta phases themselves, modeling of the inhomogeneous phases is required.…”
Section: Introductionmentioning
confidence: 99%